Effect of Corruption on Foreign Direct Investment Inflows in Nigeria (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2019)
This study investigates the effect of corruption on foreign direct investment inflows in Nigeria, by using some control variables. The study covers a period from 1996 to 2017 and employs Ordinary Least Squares method to perform the multiple regression analysis with the aid of SPSS version 20. The findings indicate that corruption has a significant positive influence on FDI. Though the influence of inflation is significantly negative but exchange rate and Nigeria‟s corruption ranking position have insignificant positive impact on FDI. The implication is that the poor legal framework and institutional qualities in Nigeria are helping corruption to thrive in all areas of Nigeria‟s economy and might ruin the young generation if nothing is done urgently. The study finds support for helping hand theory of corruption and FDI and also establishes that inflation has a significant negative influence on FDI inflows in the country. Therefore, the study recommends establishment of strong institutional and legal system to curtail the prevailing situation in order to save the future of the country.